Synthesis, biochemical evaluation and computational simulations of new cytochrome bc1 complex inhibitors based on N-(4-aryloxyphenyl) phthalimides; Chinese Chemical Letters; Vol. 29, iss. 12 - Cheng Hua; Fu Yan; Chang Qing; Zhang Ni; Bu Mengwei; Niu Yan; Wu Qiongyou; Chen Cheng; Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen